Preliminary assessment of Voisin grazing as a tool for restoring soil conditions af ter extensive grazing - Bautista-García, Germán; López-Ortíz, Silvia; Pérez-Hernández, Ponciano; Murillo-Cuevas, Félix David; Ortega-Jiménez, Eusebio; López-Collado, Catalino Jorge (REVISTA TERRA LATINOAMERICANA, 2022)
Voisin Grazing (VG) promotes harmonized management of livestock, plants, water and soil, inducing positive changes in soil properties that have been lost due to extensive grazing management. Thus, the objective of this research is to assess some physical-chemical and biological properties of soils undergoing extensive grazing by implementing VG in two grazing environments. Two paddocks dominated by dry forest early secondary vegetation (SecVeg) and two paddocks dominated by Hyparrhenia rufa (GraMon) were chosen (all sites undergoing extensive grazing). One paddock from each environment continued under extensive grazing (14 months) while VG was implemented in the other paddocks (14 months). Soil and litter samples were collected at the beginning and end of the study. Some physical and chemical properties varied due to the sampling time (P < 0.05). Bulk density (BD), total nitrogen (TN), organic matter (OM) and organic carbon (OC) improved at the end of the study, while available potassium (K) marginally increased. Soil properties also varied because of the management nested in grazing environment (P < 0.05). In SecVeg, BD (P < 0.05) and available P (P < 0.05) improved with VG, but remained the same in GraMon. In GraMon, OM (P < 0.05) and OC (P < 0.05) increased only with extensive grazing (P < 0.05). Macrofauna morphospecies abundance and richness increased with VG in both grazing environments (P < 0.05), where the order Isoptera dominated. Af ter 14 months of implementing VG, some physical, chemical, and biological soil properties had begun to regenerate.